Willingness To Pay In Kubah National Park And Matang Wildlife Centre: A Contingent Valuation Method - Nor Afiza, Abu Bakar; Alias, Radam; Zaiton, Samdin; Mohd Rusli, Yacob (Universiti Malaysia Sarawak, (UNIMAS), 2016)
National Park is an important component in the protected area system, and plays a key role in the tourism industry, precisely through ecotourism. Since its inception, the national park concept has been defined in different ways, but it is often connected with the idea of conservation and preservation of the nature and its ecosystems. Having the challenges in the determination of the value (price) of the non-market goods and services, non-market valuation techniques such as Contingent Valuation Method and Choice Experiment have been developed to cater the issues in valuing environmental goods. This study seeks to study on the association of ecotourism as a segment of tourism in Malaysia. However, the scope of this study is limited to the valuation of ecotourism of NPs in Malaysia, particularly in Kubah National Park, Sarawak. Data were obtained using questionnaires from face-to face interviews. A sample of 618 respondents, comprising of visitors and non-visitors (Kuching residents) were involved in the study.